Production of Talk Show Program “Breakout” and “Kimchi” at PRO 2 RRI Semarang (Producer) - Gabrielle P., Maria; Ratri Rahmiaji, M.Si, Dr. Lintang (Interaksi Online, 2016)
The Radio of Republic Indonesia (Radio Republik Indonesia - RRI) is the oldest and the only government’s radio which has visions to embody Indonesia public broadcasting as the extensive network radio, character development of nation, and as the world class radio. RRI has a very extensive network, from Aceh to Papua, but not many young people are interested listening to the RRI. The basic reasons of that case are the RRI image as radio news and radio for the older. Solution to overcome the matter is creating talk show programs like “Breakout” and “Kimchi” in PRO 2 RRI Semarang the paramount expectation by creating those programs is to increase the listener of RRI PRO 2 Semarang, in particular the young people. In this activity, the author served as a producer who is responsible for the continued operation of a radio broadcast program. Author tasked to conceptualize events, determine the theme and speakers, making rundown, overseeing the event and then do an evaluation at the end of the program. From several theme we found out culinary theme is the theme that most interests the listener. Result of the post-production questionnaire shows that through the production of "Breakout" and "Kimchi" talk show, we succeed to increase the number of PRO 2 RRI listeners. At first the program "Kimchi" was only 8% of the initial data we collect but then increased to 67%. While the program "Breakout" which was initially 28%, then increased to 65%. Another finding is the program "Kimchi" increased more than in the "Breakout". It is proven from the success of both talk show program that resulted from the combination of right buzzing, interesting material such as voxpop and earcatcher, good cooperation between broadcasters and sources, and a quiz with prizes.